THE EFFECT OF INSTAGRAM INFLUENCER MARKETING: WHAT AFFECTS CUSTOMER’S PURCHASE INTENTION? THE ROLE OF INVOLVEMENT IN INFLUENCER FOLLOWING AND PERCEIVED TRUST IN INFLUENCER’S BRAND RELATED CONTENT - Bogoevska-gavrilova, Irena; Ristevska jovanovska, Snezhana (University of National and World Economy, Sofia, Bulgaria, 2022)
Social media marketing allows brands to gain advantage by building relationships with customers. In that direction, influencer marketing is experiencing a rapid growth. This study is based on the integrated social media influencer value model, which among other things, examines how customers’ trust in influencer branded content and involvement level in social media influencer following affect customer’s purchase intentions. With the purpose to determine the impact of involvement in Instagram influencer following and perceived trust in Instagram influencer’s brand related content on customer’s purchase intention, this study aims to fill the gap due to lack of research, as known by the authors, by investigating involvement level and perceived trust and how they affect customer’s behavioral intention, with a focus on Instagram. Non-probabilistic purposive sampling was used to conduct an online survey to Instagram users in the Republic of North Macedonia that follow influencers. Multiple linear regression was applied to an effective set of 76 responses using SPSS, resulting in confirmation of hypotheses. At the end, a conclusion is given with the focus on theoretical contributions and practical implications that will act as recommendations for marketing-managers on how to affect customer’s purchase intention and increase sales by collaborating with Instagram influencers.
Keywords: influencer marketing, social media, involvement, trust, purchase intention